2016
DOI: 10.3389/fmicb.2016.00546
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Assessment of Stress Conditions for Simultaneous Production of Microalgal Lipids and Carotenoids

Abstract: Microalgal species are potential resource of both biofuels and high-value metabolites, and their production is growth dependent. Growth parameters can be screened for the selection of novel microalgal species that produce molecules of interest. In this context our review confirms that, autotrophic and heterotrophic organisms have demonstrated a dual potential, namely the ability to produce lipids as well as value-added products (particularly carotenoids) under influence of various physico-chemical stresses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
178
1
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(198 citation statements)
references
References 175 publications
(196 reference statements)
3
178
1
16
Order By: Relevance
“…and Scenedesmus sp. had an increased production of carbohydrates under similar conditions (Minhas et al 2016). Hence, to optimise the production of biomass alongside with high lipid yields, microalgae should be cultivated in nitrogen rich conditions for high production of biomass yield and then transferred to low nitrogen conditions for lipid production.…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhousementioning
confidence: 99%
See 2 more Smart Citations
“…and Scenedesmus sp. had an increased production of carbohydrates under similar conditions (Minhas et al 2016). Hence, to optimise the production of biomass alongside with high lipid yields, microalgae should be cultivated in nitrogen rich conditions for high production of biomass yield and then transferred to low nitrogen conditions for lipid production.…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhousementioning
confidence: 99%
“…Riano et al (2016) indicated that C.sorokinianabiomass produced 3.0-4.5% dry matter from nitrogen uptakes, whereas the nitrogen content in biomass cells ranged from 27 to 40%. The nitrogen levels in wastewater affect microalgae lipid production and growth rates by 1-10% (Minhas et al 2016) as high concentrations of nitrogen might increase the quantity of microalgae biomass. In contrast, the production of lipid and carbohydrates increases when there is nitrogen deficiency.…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhousementioning
confidence: 99%
See 1 more Smart Citation
“…However, most microalgae prefer glucose as it can easily be assimilated and produce energy-rich compounds such as neutral lipids. Glucose-grown microalgae showed higher growth rates compared to those grown on acetate and fructose [68]. The yield of lutein was found to be increased with the increase in glucose concentration in C. protothecoides [69].…”
Section: Outdoor and Indoor Cultivation Of Microalgaementioning
confidence: 79%
“…However, to reduce the cost and also to recycle industrial CO 2 , the microalgae cultivation facility should not be far away from the CO 2 source. (2) Heterotrophic cultivation: The organisms capable of heterotrophic cultivation lack the photosynthetic machinery and hence cannot generate energy through inorganic compounds oxidation [68]. Heterotrophic cultivation requires organic carbon (glucose, fructose, sucrose, lactose, galactose, mannose, acetate, glycerol, etc.)…”
Section: Outdoor and Indoor Cultivation Of Microalgaementioning
confidence: 99%